2011
DOI: 10.1051/0004-6361/201116845
|View full text |Cite
|
Sign up to set email alerts
|

TheSpitzerdiscovery of a galaxy with infrared emission solely due to AGN activity

Abstract: Aims. We present an analysis of a galaxy (SAGE1CJ053634.78-722658.5) at a redshift of 0.14 of which the infrared (IR) emission is entirely dominated by emission associated with the active galactic nucleus. Methods. We present the 5−37 μm Spitzer/IRS spectrum and broad wavelength spectral energy distribution (SED) of SAGE1CJ053634.78-722658.5, an IR point-source detected by Spitzer/SAGE. The source was observed in the SAGE-Spec program and was included to determine the nature of sources with deviant IR colours.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…In addition, two QSOs used by Anguita et al (2000) and one by Pedreros et al (2002) to study the proper motion of the LMC are attributed to a private communication by Maza in 1989 and/or do not appear in previous studies. More recently, 1 QSO was confirmed by Hony et al (2011) and 145 QSOs by Kozłowski et al (2012), the latter identified from OGLE-III light-curves. The entire MACHO database, with light-curves spanning a time range of ∼7.5 yr, was searched by Kim et al (2011Kim et al ( , 2012 who trained a support vector machine model with diagnostic features based on mid-IR colours, spectral energy distribution red-shifts and X-ray luminosity of previously known QSOs to identify 663 high confidence candidates, but none of them are at present spectroscopically confirmed.…”
Section: Appendix A: Known Qsos Behind the Magellanic Systemmentioning
confidence: 95%
“…In addition, two QSOs used by Anguita et al (2000) and one by Pedreros et al (2002) to study the proper motion of the LMC are attributed to a private communication by Maza in 1989 and/or do not appear in previous studies. More recently, 1 QSO was confirmed by Hony et al (2011) and 145 QSOs by Kozłowski et al (2012), the latter identified from OGLE-III light-curves. The entire MACHO database, with light-curves spanning a time range of ∼7.5 yr, was searched by Kim et al (2011Kim et al ( , 2012 who trained a support vector machine model with diagnostic features based on mid-IR colours, spectral energy distribution red-shifts and X-ray luminosity of previously known QSOs to identify 663 high confidence candidates, but none of them are at present spectroscopically confirmed.…”
Section: Appendix A: Known Qsos Behind the Magellanic Systemmentioning
confidence: 95%
“…They can be seen in emission in galaxies, when the dust is hot enough (T 150 K). It is the case near the central engine of AGNs (Wu et al 2009;Hony et al 2011), even low-luminosity AGNs, like the nucleus of M 31 (Hemachandra et al 2015). The MIR spectra of earlytype galaxies also show clear silicate emission features, but likely of circumstellar origin (e.g.…”
Section: Milky Waymentioning
confidence: 99%
“…It is SSTISAGEMC J053634.77−722658.6 (OB-JID 151), however, which turned out to be the most intriguing. Hony et al (2011) argued that the lack of far-IR emission and the optical and near-IR faintness indicate that the mid-IR emission is dominated by the AGN torus; this galaxy has the largest silicate-to-continuum ratio known. Subsequently, van Loon & Sansom (2015) obtained optical spectra with the Southern African Large Telescope (SALT), refining the redshift to z = 0.1428 and discovering strong, broad Hα emission from near the AGN and relatively narrow stellar absorption in the spectrum of an early-type galaxy.…”
Section: The Sample Of Galaxiesmentioning
confidence: 99%